Research on the Modernization of China Foreign Commercial Arbitration: From the Perspective of Building an International Commercial Arbitration Center - Ji, Jiaqi (Transactions on Social Science, Education and Humanities Research, 2024)
Under the background of social change and the great development of "Belt and Road" policy, China's international commercial arbitration is facing a higher level of development needs. In order to solve the existing problems, draw on the experience of the world's advanced international arbitration centers, improve the concept of arbitration, and improve the level of arbitration services, China should take the goal of building a China international commercial arbitration center comparable to the world-class level, and constantly explore the development path of arbitration. This paper analyzes the present situation and trend of international commercial arbitration in China, discusses the connotation and value of China international commercial arbitration center, put forward from government relations, institutional development, system architecture, modernization can assign four aspects to improve the arbitration center construction scheme, and innovatively put forward the horizontal and vertical two lines and special assigned to the development of the framework. Accordingly, China's international commercial arbitration system should be continuously improved, the credibility and discourse power of China's international commercial arbitration should be enhanced, and China should build an international arbitration brand with Chinese characteristics.